All It Takes Is One: The Effect of Weakest-Link and Summation Aggregation on Public Good Provision under Threshold Uncertainty - Fredrik Carlsson; Claes Ek; Andreas Lange (Center for Economic Studies and ifo Institute (CESifo), 2021)
We report experimental evidence on the voluntary provision of public goods under threshold uncertainty. By explicitly comparing two prominent technologies, summation and weakest link, we show that uncertainty is particularly detrimental to threshold attainment under weakest link, where low contributions by one subject cannot be compensated by others. In contrast, threshold uncertainty does not affect contributions under summation. We demonstrate non-binding pledges as one mechanism to improve chances of threshold attainment under both technologies, yet in particular under weakest link.
Keywords: C91; H41; Q54; 330; public goods; threshold uncertainty; weakest link; coordination; experiment